Preparation and characterization of rice husk ash (RHA)-TiO2 / ZnO composites and its application in treating effluents from textile industries - Kabir, MH; Kabir, MF; Nigar, F; Ahmed, S; Mustafa, AI; Ahsan, M (Bangladesh Journal of Scientific and Industrial Research, 2013)
Photocatalytic composite materials incorporating the photocatalysts (TiO2, ZnO) with rice husk ash (RHA) have been developed to investigate the photodegradation of real textile dye effluent. The structural characterization of the composite materials was performed using XRD (X-Ray Diffractometer). The characteristic XRD peaks together with the 2? values for both TiO2 and ZnO were in excellent agreement with the standard JCPDS d-values. The efficacy of these composites was examined through the degradation of a textile dye, collected from a local dye house. The sun light was used as the source of illumination for the preceding degradation reaction. Bangladesh J. Sci. Ind. Res. 47(4), 445-448, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14075